Response potential assessment of user-side flexible resources of regional power distribution networks based on sequential simulation of optimal operation - Li, Wensheng; Liang, Rong; Luo, Fengzhang; Feng, Shaoting; Yang, Bo; Liu, Zhao; Li, Zhao; Zhang, Wen; Kong, Kuangyu; Lu, Siyuan (Frontiers in Energy Research, 2022)
In order to reasonably consider the support capability of multiple types of flexible resources for power grid planning and operation, this paper proposes an assessment method of response potential of end-user-side flexible resources of regional power distribution networks based on sequential simulation of optimal operation. First, the response potential evaluation framework and the evaluation index are proposed. Then, based on the idea of time series simulation of optimal operation of distribution network, the response potential evaluation model considering the interactions between flexible resources and power grid is constructed and solved by optimization package. Finally, the validity of the proposed evaluation method is verified by an actual case from a certain area in northern China. The analysis results show that the end-user-side flexible resources are a kind of balanced resources with good economy, and it is necessary to take the response potential assessment of flexible resources into account in the planning of future new type distribution networks.